Identification of the nitrate and nitrite content in leafy vegetables from the city of Zliten - Ajaj, Ismail A; Zeglam, Zubaida; bin Fayed, Ibtisam; Sheneeb, Marwa; Al-Ahmar, Rabia Abdel Qader; Abu Mahal, Wedad Muhammad (Journal of agricultural, environmental and veterinary sciences, 2021)
The study identifies the nitrate (NO3) and nitrite (NO2) content in leafy vegetables (parsley, chard, coriander) in three agricultural areas in Zliten (Azdo, Dafniya, Madjer) using the colorimeter dr / 980 device, and assesses whether the content is within the comparatively with allowable concentrations. The results obtained from this study show that the nitrate concentrations in all samples examined are within the global standards, with the highest level of 5.5 ppm found in chard samples collected from the area of Azdo. As for nitrite, the concentrations found in the studied samples are higher than nitrate concentrations. Overall, the nitrate and nitrite content are found to be within the permitted concentrations based on international standards, where the highest concentration of nitrite of 60 ppm is recorded in parsley samples from the Dafniya area.